2014
DOI: 10.4081/or.2014.5334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes assessment of three similar hip arthroplasty bearing surfaces

Abstract: This report examines the clinical performance of three very similar total hip arthroplasty designs with distinctly different bearing surfaces used over the course 10-17 years. Clinical outcomes assessments for each group are compared in the context of varying implant related costs related to the latest technology at the time of surgery. Eighty-one surgeries were studied and differ by bearing surface. In this study, 36 hips are ceramic on polyethylene, 27 are metal on polyethylene and 18 are metal on metal. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This is quite similar to the 9.8% rate of dislocation using the same stem design with unconstrained cups. 27 , 28 Patients in the current series with occasional positional clicking remain pain free without compromise in the function of their arthroplasties.…”
Section: Discussionmentioning
confidence: 81%
“…This is quite similar to the 9.8% rate of dislocation using the same stem design with unconstrained cups. 27 , 28 Patients in the current series with occasional positional clicking remain pain free without compromise in the function of their arthroplasties.…”
Section: Discussionmentioning
confidence: 81%
“…Two additional studies by Parsons et al 27 and Bjorgul et al 28 comparing MoP and CoP bearings found similar infection rates, but again were unable to establish strong associations due to size limitations. Bozic et al 29 compared revisions rates between MoM, MoP, and CoC implants, finding lower infection rates in MoP bearings compared to the MoM, but similar incidence of both all-cause revisions and PJI between the MoP and CoC.…”
Section: Resultsmentioning
confidence: 94%
“…Parsons C et al (2014) compared the clinical outcomes of three bearing surfaces (MoM, MoP, CoP). 14 They studied the outcome of 81 primary THA patients with an average follow-up of 8.6 years. They concluded that the rates of pain, complications and need for revision secondary to articular wear are similar among the 3 bearing surfaces compared.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the rates of pain, complications and need for revision secondary to articular wear are similar among the 3 bearing surfaces compared. 14 Dongcai et al, in 2015 did a meta-analysis of randomized controlled trials to compare the outcome of ceramic-on-ceramic and metal-onpolyethylene bearing surfaces. 2 There was no difference in functional outcome as measured by Harris hip score between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%